The Influence Of Financial Literacy And E-Commerce On Student Consumptive Behavior - Adinda Syahla; Sudrajat Sudrajat (Yayasan Riset dan Pengembangan Intelektual, 2023)
Consumptive behavior is one of the behavior of buying goods that is not based on a need but a desire that must be realized. It is very easy for Indonesian people, especially students, to enter into a consumptive lifestyle. This is caused by the lifestyle of students who do not have the right priorities, such as spending that exceeds their financial capabilities and does not meet their needs. This study aims to determine whether financial literacy and E-commerce have an influence on consumptive behavior. This research was conducted by involving students of S1 Accounting at the University of Lampung with a total sample of 109 students. The analytical method used in this study is a quantitative method with primary data as the source of research. The method of determining the sample is based on the non-probability sampling method using purposive sampling technique. The data that has been collected is then analyzed using the Partial Least Square (PLS) Analysis method approach. The results of this study concluded that financial literacy has a negative influence and shows no significant relationship to the consumptive behavior of S1 Accounting students at the University of Lampung and vice versa E-Commerce has a positive and significant influence on the consumptive behavior of S1 Accounting students at the University of Lampung.